Massive Left Atrium from Severe Mitral Stenosis due to Rheumatic Heart Disease: Clinical Images Not Usually Seen in Modern Radiology and Ultrasound - S Lane, Andrew; J Clancy, David; M Seppelt, Ian; R Orde, Sam (Journal of Clinical Case Reports and Images, 2019)
Rheumatic heart disease is becoming far less common in the developed world, and therefore expsoure to its complications are been seen less by clinicians. With the increasing ease of world travel, patients with less commonly seen medical conditions are increasingly presenting to Hospitals requiring management of their complications. We present a case of an elderly lady who was a tourist in Australia, who presented with complications of her rheumatic heart disease, and her subsequent radiological and echocardiographic investigations were a significant surpirse for her treating clinicians.
Keywords: Rheumatic heart disease; Echocardiography; Massive Left Atrium